Basic Principles of Language Learning - Rakhmad Agung Hidayatullah; Ari Hasbya; Husna Maulida Hasanah; Nabila Aulia Risyad (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2026)
Language is a defining characteristic of human beings and serves as a means of communication and interaction among social beings. It is the existence of language that imbues human life with culture. Language acts as a medium for developing human thought, particularly in articulating the reality of the world around us. Learning principles represent an educator's efforts to create and structure the learning environment so that students can engage in learning activities optimally. Consequently, educators must understand these principles, their application, and the challenges involved in implementing them. Therefore, adapting to the evolution of the times and technology is crucial for creating effective and engaging language learning experiences.